Triggers of mental health indicators in women of migration zones (Zacatecas) with or without a migrant partner - Acevedo Sánchez, Carlos Ernesto (Consorcio de Universidades Mexicanas A.C., 2017)
The migratory process modifies the day to day life of women with an immigrant husband changing their psychic health and creating sick conditions. For this reason the object of this research is to know if the traditional and emerging zones and age are factors that influence the prevalence of the diverse indicators of mental health in women married and not married to an immigrant in the high migrant incidence zones of the state of Zacatecas. To get this information applied a questionnaire in a sample of 279 women in the towns of Jerez and Juan Aldama in which 144 were not married to a migrant and 135 with a migrant husband. The result shows that the traditional and emerging zones and age are factors that influence this prevalence of the depression, interpersonal sensitivity and anxiety in women who reside in zones of high migratory incidence in the state of Zacatecas.